Fibre-Vessel Structure, Density and Moisture Content Analysis of Zanthoxylum gilletii Wood with Comparative Evaluation Against Enthandrophragma cylindricum for Furniture Use - Domekyiir, Delle Desire; Appiah-Kubi, Emmanuel; Kwaku, Antwi; Awotwe-Mensah, Michael (European Journal of Applied Sciences, 2026)
The density of wood is among several factors that influence the strength and durability of wood. However, scanty research is carried out on the effect of anatomical characteristics of wood. Fibre and vessels were sampled from three Ghanaian timbers, Zanthoxylum gilletii (Okuo) and Enthandrophragma cylindricum (Sapele) each. The study performed is to assess some key measurements; fibre length (FL), vessel diameter (VD), fibre diameter (FD), fibre lumen width (FLW), and fibre wall thickness (FWT) and density of wood of the selected tree. Results indicated highly significant (p<0.05) (Table 2) Specific variations revealed that Z. gilletii has the greatest fibre-vessel content and high density than E. cylindricum but was less moisture content to E. cylindricum. In terms of density, Z. gilletii ranged from 716 to 842 kg/m³, exceeding E. cylindricum range of 640 to 758 kg/m³ (Fig. 1). Fibre diameter for E. cylindricum ranged from 19.35 to 24.12 µm, whereas Z. gilletii showed slightly narrower fibres between 18.99 and 19.58 µm (Table 1). Overall, the denser, vessel-rich anatomy of Z. gilletii indicated a its high strength to buttress its potentials as a durable and efficient substitute for E. cylindricum and some well-known timber species (WKS) in furniture and structural applications. The higher density of Z. gilletii, combined with its lower moisture content, suggests enhanced resistance to fungal and insect damage and mechanical strength.